How the Political Trust Before, at Pandemic and Vaccinations: Provincial Case Studies in Indonesia (2019, 2020 and 2021) - Dadang Mas Bakar; Agus Adriyanto; Nur Rezki Amalia (Jurnal Studi Pemerintahan, 2022)
The Covid-19 pandemic caused various problems. Government and political systems were also disrupted, including political trust. This study aims to compare the level of youth political trust to government and parliament before pandemic (2019), at the pandemic (2020), and when the vaccine starts (2021), collecting data using a questionnaire on institutional political trust in 1122 respondents taken at three different years. Data were collected using stratified cluster random sampling, which is spread across 14 districts in South Sulawesi. Then, the data were analyzed using the Anava test using SPSS 24.0. The results analysis found show that youth's trust in government during 2019-2021 were ups and downs, which before the pandemic trust was at 62%, then when the pandemic fell to 55% and in 2021 it could be increased again by the government to 60% which it means that only a difference of 2% from before the pandemic. Youth trust in the DPRD during 2019-2021 has had ups and downs, wherein in 2019, the level of trust was at 50%. Then at the pandemic (2020), it increased to 53%, and in 2021 after vaccines and government programs running well, it decreased far from before the pandemic to 50%.